2020
DOI: 10.1016/j.jcmgh.2019.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Biotin Supplementation Ameliorates Murine Colitis by Preventing NF-κB Activation

Abstract: Biotin deficiency causes an inflammatory bowel disease-like state, but biotin supplementation has never been tested as a therapeutic in established models for inflammatory bowel disease. We found that biotin therapy leads to delayed onset and severity of dextran sodium sulfate colitis mediated by decreased activation of nuclear factor-kB. BACKGROUND & AIMS: Biotin is a water-soluble vitamin that is indispensable for human health. Biotin deficiency can cause failure-to-thrive, immunodeficiency, alopecia, dermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 51 publications
(71 reference statements)
1
24
0
Order By: Relevance
“…In the current study, 6 the authors showed that biotindeficient diet was able to induce a colitis like phenotype in mice, which was alleviated with biotin supplementation. In addition, dextran sulfate sodium (DSS)-induced colitis mice also showed biotin deficiency along with significantly reduced levels of sodium-dependent multivitamin transporter (SMVT) involved in biotin absorption.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…In the current study, 6 the authors showed that biotindeficient diet was able to induce a colitis like phenotype in mice, which was alleviated with biotin supplementation. In addition, dextran sulfate sodium (DSS)-induced colitis mice also showed biotin deficiency along with significantly reduced levels of sodium-dependent multivitamin transporter (SMVT) involved in biotin absorption.…”
mentioning
confidence: 55%
“…5 Deficiency of vitamins in B complex, specifically thiamine (B1) and biotin, were suggested to be potential culprits in the development of this symptom. 5 In the current issue of Cellular and Molecular Gastroenterology and Hepatology, Skupsky et al 6 provide novel evidence of the role of biotin in UC. Biotin, also known as vitamin B7 or H, is not synthesized in humans; therefore, dietary intake and bacterial synthesis in the gut are its main sources.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, its possible involvement in the NF-κB pathway regulation holds high expectations in a potential antiinflammatory process. Recently, this hypothesis has been strengthened by Skupsky et al, which showed a lowered NF-κB activity and histological signs of mucosal inflammation in the colon of biotin-supplemented mice [ 128 ]. This observation concurs with a previously mentioned study, exploring the supplementation of VB5 and VB8 [ 110 ].…”
Section: Microbiota-derived Metabolites That Modulate Host Immunity In the Gutmentioning
confidence: 99%
“…After stimulation through TLRs, proinflammatory cytokines or antigen receptors, I-κB is phosphorylated, ubiquitinated, and finally proteolytically degraded, leading to de-repression of NF-κB, which rapidly translocate to the nucleus and activates the transcription of several target genes [ 112 ]. It has also been thoroughly established that intestinal inflammation occurring in IBD is accompanied by an NF-κB driven overexpression of pro-inflammatory adhesion molecules and mediators, leading to disturbances in mucosal immunity [ 113 , 114 ].…”
Section: Molecular Mediators Of Lymphangiogenesis In Ibdmentioning
confidence: 99%